Analysis of the Factors Affecting Trade Balance in Indonesia - R. , Roosaleh Laksono; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
which means that Indonesia’s export value has decreased and imports have tended to increase. While the Indonesian domestic currency (IDR) has depreciated against several other currencies, including the American currency (USD). In theory, it would be explained that if the currency of a domestic currency depreciates, then exports should increase because the commodity of the country is competitive compared to other countries in the international market, whereas the government will limit imported commodities because imported goods will be increasingly expensive. This arises from the occurrence of research gaps. export value, import value, exchange rate, and GDP on the trade balance, especially in Indonesia in the short and long term. The results of the study explained that in the long term for 35 years (1980–2015), referring to all independent variables (export value, import value, exchange rate, and GDP) significantly affected the trade balance of 55.08 percent, while the remainder was explained by other variations that were not included in this research model. However, in the short term, the results of the co-integration test and error-error method show that all independent variables do not occur in the short-run equilibrium relationship with the dependent variable. All independent variables are inversely proportional to trade balance.